ANALISIS SALURAN PEMASARAN SELADA HIDROPONIK DI POJOK SAYUR KECAMATAN MARTAPURA KABUPATEN OKU TIMUR - Iman Sulaiman, Andri Irawan, Neng Karmila, Leni Sabrina, (JASEP, 2024)
Cultivating vegetables with a hydroponic system is one way to improve the quality of vegetables, one of which is green lettuce. Green lettuce has good benefits for the body. This study aims to analyze the marketing channels of hydroponic lettuce. This research was conducted at the hydroponic vegetable business "Pojok Sayur" Terukis Rahayu Village, Martapura District, East OKU Regency. The research method used in this study is the case study method. The sampling method used is the census method. Marketing channels are analyzed descriptively using the marketing margin formula. Based on the results of the research that has been done, it can be concluded that there are two lettuce marketing channels in Pojok Sayur, Martapura District, namely direct marketing channels (Marketing Channel I) and indirect (Marketing Channel II). Marketing margin analysis shows that the margin obtained in marketing channel I is IDR 47,000.00, while in marketing channel II it is IDR 45,000.00.